Pencegahan dan Pemberantasan Tindak Pidana Gratifikasi - A. Melantik Rompegading (CV. Social Politic Genius (SIGn), 2021)
This study examines the principles that can deter and eradicate gratification as part of the corruption crime. This study uses a normative juridical research method. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal material is then analyzed using qualitative data analysis methods, which will conclude the research's object. The results show that the deterrence and eradication of gratification crime have been regulated in Article 12 B and Article 12 C of Law No. 20 of 2001. In addition, this provision contains an encumbrance of reverse proof, which aims to simplify the process of proving illegal receipts and indications as a bribery crime for civil servants or state administrators. The principles in deterrence and eradication of gratification crime include legal certainty, transparency, accountability, public interest, proportionality, and respect for human rights. Therefore, it is recommended to CEC, civil servants or state administrators, and the community to practice the principles of deterrence and eradication of gratification crime. In this case, Indonesia can be released from the shackles of criminal acts of corruption in the future.